Impact of hepatic steatosis on the efficacy of antiviral treatment for chronic hepatitis B and the establishment of predictive model: a cohort study - Guanghui Ren; Kaining Jia; Shi Yin; Yunpeng Guan; Qingwei Cong; Ying Zhu (Virology Journal)
Abstract Aim Metabolic dysfunction-associated steatotic disease (MASLD) and chronic hepatitis B (CHB) are prevalent liver disorders. Ongoing discussions investigate the impact of MASLD on the therapeutic outcomes of CHB. Methods A cohort of 320 CHB patients on antiviral therapy (including NAs and PEG IFNα) were included and categorized into CHB + MASLD (n = 125) and CHB group (n = 195). The treatment response rates, Kaplan–Meier survival analysis, and Cox regression were assessed between the two groups to investigate the impact of MASLD on antiviral responses in patients with CHB. Results At weeks 24 and 48, the CHB + MASLD group displayed a higher HBsAg response rate than the CHB group (24 weeks: 11.5% vs. 3.8%, p = 0.026; 48 weeks: 24.4% vs. 8.4%, p = 0.001). The pgRNA response was also higher in the CHB + MASLD group at both time points (24 weeks: 30.9% vs. 19.7%, p = 0.163; 48 weeks: 48.8% vs. 28.3%, p = 0.049). Kaplan–Meier survival analysis revealed a shorter median time to HBsAg response at 48 weeks for the CHB + MASLD group (HR = 3.251, 40 weeks vs. 42.5 weeks, p = 0.002). This is particularly evident among individuals who are negative for HBeAg (48w: 24.2% vs 12.2%, p = 0.005). KM survival analysis demonstrated that the CHB + MASLD group was more likely to achieve HBsAg response (HR = 2.428, p = 0.039).COX regression analysis identified age (HR = 0.948, p = 0.005), antiviral regimen (NAs + PEG IFNα: HR = 5.33, p < 0.001; PEG IFNα: HR = 1.099, p = 0.93), baseline HBsAg level (HR = 0.648, p = 0.009), and MASLD presence (HR = 3.321, p = 0.002) as independent predictors for HBsAg response. Time-ROC analysis showed that these factors effectively predicted HBsAg decline (24 weeks: AUC = 0.902; 48 weeks: AUC = 0.890). The model demonstrated strong discriminative power, calibration, and clinical relevance. Conclusion In CHB patients without significant liver fibrosis who receive antiviral therapy, concurrent MASLD enhances HBsAg response, particularly in HBeAg-negative patients. Factors like younger age, NAs with PEG IFNα therapy, lower initial HBsAg levels, and MASLD presence predict treatment success. Further investigations are required to elucidate the impact of diverse metabolic disorders on the advancement of liver fibrosis. Trial registration Registry and the registration No. Of the study/trial: ChiCTR23000 74064(2023-07-28).